PENGARUH KEBIJAKAN DIVIDEN, TAX MINIMIZATION DAN TUNNELING INCENTIVE TERHADAP PRAKTIK TRANSFER PRICING - Saragih, Muhammad Rizal; Rusdi, Rusdi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to determine the effect of Dividend Policy, Tax Minimization and Tunneling Incentives on Transfer Pricing practices. The type of research is quantitative using descriptive methods. The sampling method used was a purposive sampling method with a total sample of 21 non-cyclical consumer sector companies listed on the Indonesian stock exchange in 2018-2022 with a population of 113 companies. The research findings reveal that dividend policy and tax minimization strategies do not significantly impact transfer pricing practices. This suggests that companies’ decisions on distributing dividends and minimizing taxes are not directly related to how they engage in transfer pricing. Transfer pricing, in this context, appears to be unaffected by these financial strategies, indicating that factors like shareholder returns and tax planning are not influencing the way companies set prices for transactions between their subsidiaries. This implies that when shareholders have strong incentives to divert resources, it can influence how transfer pricing is set. Additionally, the research finds that when considering all three factorsdividend policy, tax minimization, and tunneling incentives—together, they do collectively influence transfer pricing practices.